1999
DOI: 10.1017/s0958067099018266
|View full text |Cite
|
Sign up to set email alerts
|

The use of a deuterium tracer technique to follow the fate of fluids ingested by human subjects: effects of drink volume and tracer concentration and content

Abstract: summaryDeuterium oxide (ÂHµO) has been added to drinks as a tracer for water to estimate the availability to the body water pool of ingested fluids, but doubts have been raised as to the reliability of the method. The present investigation evaluated the effects of systematic variations in the volume of fluid consumed and the amount and concentration of added tracer on the rate of accumulation of tracer in arterialized blood after ingestion of a labelled drink. Three separate experiments were undertaken. In exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Intervening sampling was performed using saliva. Our data agree with those of others [42][43][44] that showed that salivary isotopic enrichment is a suitable surrogate for enrichment of tracer in blood, allowing calculation of total fluid absorption. This sampling route, however, was not suitable for the determination of uptake rates because despite exhortations to rinse the mouth thoroughly, the initial peak in D 2 O enrichment in saliva seen in some subjects indicated that some isotope in the ingested fluid remained in the oral cavity.…”
Section: Discussionsupporting
confidence: 92%
“…Intervening sampling was performed using saliva. Our data agree with those of others [42][43][44] that showed that salivary isotopic enrichment is a suitable surrogate for enrichment of tracer in blood, allowing calculation of total fluid absorption. This sampling route, however, was not suitable for the determination of uptake rates because despite exhortations to rinse the mouth thoroughly, the initial peak in D 2 O enrichment in saliva seen in some subjects indicated that some isotope in the ingested fluid remained in the oral cavity.…”
Section: Discussionsupporting
confidence: 92%
“…After ingestion the water is readily transported across the mucosal membrane of the alimentary canal and diffuses into the blood within 2 min (Davis et al, 1985;Lambert et al, 1999). Next, the water moves via capillary fluid exchange from the intravascular to the extravascular space in approximately 30 s (Cao et al, 2005;Oppenheimer et al, 1983).…”
Section: Discussionmentioning
confidence: 99%
“…It is well documented, that following ingestion, water is rapidly absorbed by the gastrointestinal mucosa and within 2 min starts to appear in the plasma, thus maintaining blood volume (Davis et al, 1985;Lambert et al, 1999). However, it is currently unknown how long it takes following ingestion for water to start to appear as sweat on the skin surface, which would be available for evaporative cooling.…”
Section: Introductionmentioning
confidence: 99%
“…Although it does not directly measure net fluid movement across the intestinal wall, it still provides a useful index of fluid availability (13). The accumulation of D 2 O in plasma, urine, and saliva has been used as an index of the in vivo kinetics of these fluids (1,10,16,18). It rapidly equilibrates with these media and can be used to compare fluid availability during rest and exercise.…”
Section: Introductionmentioning
confidence: 99%